ORGANIC CARBON IN SURFACE SEDIMENTS OF LAPTEV SEA AND EAST SIBERIAN SEA: OBSERVATION OF PYROLYSIS DATA - Elena V. Gershelis; Alexey S. Ruban; Denis V. Chernykh; Natalina A. Poltavskaya; Igor P. Semiletov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Ongoing global warming accelerates release of relict terrigenous organic carbon from permafrost onto the Arctic shelf waters. When transported in the land-sea system, it can further be accumulated in bottom sediments in the shelf or deep-sea zone and undergo degradation and remineralization, which leads to critical environmental consequences. This study aims at assessing the sources and degradation degree of terrigenous organic matter in the surface sediments of the Eastern Arctic seas. Within this study, marine bottom sediments taken from the surface horizon (0–10 cm) were investigated. Sampling was carried out during the 2011–2019 marine research expeditions. Lateral consistency of hydrogen index values in modern marine sediments on the Eastern Arctic shelf (mainly in the Laptev Sea) is associated with the great contribution of heterogeneous biolabile terrestrial organic matter, in contrast to other Arctic waters, where growing hydrogen index values are associated with the consistently growing contribution of autochthonous organic matter with increasing distance from the coast. While considering the δ13C and HI/OI correlation, there are also significant deviations from the linear dependence which usually indicates a conservative marine geochemical regime. Sediments of the Buor-Khaya Bay are characterized by an increased HI/OI values in contrast to the deep-water sediments of the continental slope which shows lower hydrogen content and a higher proportion of oxygen-containing compounds, indicating a strong transformation of organic matter. These findings confirm a key role of terrigenous supply in specific biogeochemical conditions in the studied area and reveal that geochemical indicators of immature organic matter sources in the Eastern Arctic seas should be interpreted differently from other Arctic continental margins.